Kompetensi Sosial Guru Pendidikan Agama Islam dalam Pembinaan Karakter Siswa di SMA Negeri 12 Banda Aceh - Auliawati, Sitti (Jurnal Riset dan Pengabdian Masyarakat, 2025)
Teachers are required to have adequate social competence to establish effective communication and interaction with students, fellow educators, and education staff, parents or guardians of students, and the community. Teachers who are able to implement their social competencies optimally directly provide positive role models who can become role models for students. This research aims to identify the social competence of Islamic Religious Education (PAI) teachers and their relevance in developing student character, the opportunities and challenges faced in this process, as well as the efforts made by PAI teachers to develop their social competence at SMA Negeri 12 Banda Aceh. This research uses a qualitative approach with data collection methods in the form of observation, interviews, and documentation. The research results show: First, the social competence of PAI teachers: PAI teachers at SMA Negeri 12 Banda Aceh demonstrate the ability to communicate and establish good relationships with various parties, be inclusive, be objective, non-discriminatory, and be able to adapt well to their place of work. Second, the relevance of social competence in developing student character: PAI teachers' social competence has a positive influence on the formation of student character because students tend to imitate the teacher's behavior as a role model. Third, opportunities and challenges: Opportunities for successful character development are supported by the school principal, colleagues, and the participation of parents and guardians. However, the main challenge comes from the influence of peers and internal factors of students who are less motivated to improve their character. Fourth, efforts to develop social competence: PAI teachers actively participate in social activities and take part in training to improve their social skills.